(3BQGA GbJUGOjI hGLJeGYjIs - (3YHO GdCejQ QMjeI(B, (3GdYHhOs ((3YeGf(B:s (3OGQ OLdI fGTQhf hehRYhf(B,s, 2011)
(3MQH GdYedGJ eXGgQgG hJWhQgG aj Xd GdJMhdGJ aj GdfXGe GdfbOj GdOhdj(B- (3CReI GdfbO GdOhdj aj GdfXGe GdQCSeGdjs
Keywords: (3GdEbJUGOs; (3GdEbJUGO GdOhdjs; (3OQGSGJ(B- (3GdEbJUGO GdOhdjs